DEBTOR COMMITMENT IN THE IMPLEMENTATION OF WAKALAH - Muhammad Zulhilmi (JURISTA: Jurnal Hukum dan Keadilan, 2018)
The purpose of this research is to find out how the wakalah contract at Bank Aceh Syariah Capem IAIN-Darussalam on the purchase of ma'qud alaih in murabahah financing is also to find out how the debtor's understanding of the wakalah contract on the delegation of the purchase of murabahah financing objects and to find out how the debtor's consistency in implementing the wakalah contract in purchasing murabahah financing objects. From the results of further analysis, it is known that the implementation of wakalah in purchasing ma'qud alaih murabahah financing at the applicable Sharia'ah Bank is in accordance with the provisions of Fiqh muamalah, fulfilling the pillars and conditions. However, the lack of understanding of the debtor and the lack of understanding of the debtor's consistency in the implementation of the wakalah contract causes the position of the ma'qud alaih to be confusing because the object in the wakalah contract is also the object in the murabaha contract.